Unobserved structural shifts and asymmetries in the random walk model for stock returns in African frontier markets - David dde Villiers; Natalya Apopo; Andrew Phiri (Cogent Economics & Finance, 2020)
The purpose of this study is to examine the weak-form market efficiency hypothesis (EMH) for 8 African Frontier markets between 2001 and 2017. To achieve this purpose, we employ unit root testing procedures which are robust to both nonlinearities and smooth structural breaks, making this study the first of its kind for African markets. Our empirical findings suggest that, regardless of whether daily or weekly series are employed, most African frontier markets are not market efficient, in the weak sense form, with the exception of the Kenyan stock market and to a very much lesser extent the Botswana and South African stock series. Important policy and investor implications are drawn in our study.
Keywords: C21; C22; C51; G14; 330; Africa; efficient market hypothesis (EMH); unit roots; nonlinearities; unobservedstructural breaks; Fourier approximation